Penguatan Civic Engagement Generasi Z melalui Pendidikan Kewarganegaraan - Friska Putri; Susiba Susiba; Kittin Andila; Nur Anita; Qori’ah Febriyanti (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Generation Z is recognized as a digital-native generation raised in an era of rapid technological and informational development. Despite their broad access to information, they face challenges in civic participation due to issues such as national identity crises and limited critical literacy. Civic Education (PKn) serves as a crucial strategy to foster civic engagement by instilling the values of democracy, social justice, and collective responsibility through active, contextual, and technology-based learning approaches. This article is a literature review that synthesizes research findings from 2020 to 2025 regarding the role of Civic Education in enhancing political, social, and digital participation among Generation Z in Indonesia. The findings indicate that the integration of social media, volunteer activities, and community-based citizenship projects facilitated by Civic Education can strengthen critical awareness and active public involvement. Thus, adaptive and participatory Civic Education proves relevant in reinforcing civic engagement in the digital age.